2021
DOI: 10.1016/j.heliyon.2021.e07234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wind energy potential and economic evaluation of four wind turbine models for the east of Iran

Abstract: This study examined the potential of wind energy in 22 regions in eastern Iran. In this regard, it investigated the parameters of Weibull, mean wind speed, and wind power density in these areas. The results showed that the mean wind speed was above 4 m/s at all stations and in ten stations was above 5 m/s. Also, the study of monthly wind speed fluctuations in eastern parts of Iran and its comparison with the relevant variations of electricity consumption showed that the fluctuations of speed is clearly in line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The study also indicates that the sanctions have slowed Iran's progress in nuclear energy (Mohamadi et al, 2021). Furthermore, a Center for Strategic and International Studies (CSIS) study found that the sanctions have signi cantly impacted Iran's nuclear program by reducing its access to nancing and foreign technology.…”
Section: Thematic Analysismentioning
confidence: 96%
“…The study also indicates that the sanctions have slowed Iran's progress in nuclear energy (Mohamadi et al, 2021). Furthermore, a Center for Strategic and International Studies (CSIS) study found that the sanctions have signi cantly impacted Iran's nuclear program by reducing its access to nancing and foreign technology.…”
Section: Thematic Analysismentioning
confidence: 96%
“…Hence in case speed of wind is presumed to be fixed, the value of 𝑃 𝑐 hinge on the speed of rotor of the wind turbine. So, power output of the turbine is regulated by regulating the rotor speed [19].…”
Section: Mathematical Model Of Wind Turbine Systemmentioning
confidence: 99%
“…Negative impacts of greenhouse gas (GHG) on environment and security of energy supplies have made the government organizations to increase the exploitation of various sources of renewables. Wind energy is one of the clean and inexhaustible sources of renewables and it can be utilized for the generation of electricity by means of wind turbines [1,2].…”
Section: Introductionmentioning
confidence: 99%